2021
DOI: 10.1038/s41477-021-01020-x
|View full text |Cite
|
Sign up to set email alerts
|

The cryo-EM structure of the chloroplast ClpP complex

Abstract: Protein homeostasis in plastids is strategically regulated by the protein quality control system involving multiple chaperones and proteases, among them the Clp protease.Here we determined the structure of the chloroplast ClpP complex from Chlamydomonas reinhardtiiby cryo-EM. ClpP contains two heptameric catalytic rings without any symmetry. The top ring contains one ClpR6, three ClpP4 and three ClpP5 subunits while the bottom ring is composed of three ClpP1C subunits and one each of the ClpR1-4 subunits. ClpR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…Remarkably, we identified seven out of eight subunits of the plastid-localized ClpP protease complex, which was specifically identified in the CPN20 co-IPs, except for chloroplast-encoded ClpP1 being also enriched in the CPN60 co-IP (Table 1). This is consistent with previous reports that the co-chaperonin complex co-purifies with the ClpP protease when isolated from Chlamydomonas lysates (Wang et al, 2021), indicating that proteins with high r - and low q -values are good candidates for chaperonin substrate or partner proteins.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Remarkably, we identified seven out of eight subunits of the plastid-localized ClpP protease complex, which was specifically identified in the CPN20 co-IPs, except for chloroplast-encoded ClpP1 being also enriched in the CPN60 co-IP (Table 1). This is consistent with previous reports that the co-chaperonin complex co-purifies with the ClpP protease when isolated from Chlamydomonas lysates (Wang et al, 2021), indicating that proteins with high r - and low q -values are good candidates for chaperonin substrate or partner proteins.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, CPN20 was previously found to interact with ClpP protease subunits and might even directly or indirectly bind to the ClpC machinery (Kim et al, 2015, Rei Liao et al, 2022). Recently, it has been shown that the CPN23/CPN20/CPN11 lid complex associates with the purified ClpP protease complex, and that the co-chaperonin negatively affects its catalytic activity (Wang et al, 2021). It was hypothesized that this interaction serves to reduce the proteolytic capacity of ClpP and folding via CPN60 at the same time, since the lid is prevented from encapsulating substrates within the CPN60 cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, we identified seven out of eight subunits of the plastid-localised ClpP protease complex, which was specifically identified in the CPN20 co-IPs, except for chloroplastencoded ClpP1 being also enriched in the CPN60 co-IP (Table 1). This is consistent with previous reports that the co-chaperonin complex co-purifies with the ClpP protease when isolated from Chlamydomonas lysates (Wang et al, 2021), indicating that proteins with high r values and low q values are good candidates for chaperonin substrate or partner proteins. q values are based on correlation p values that were obtained using jackknife cross-validation.…”
Section: Identification Of Cpn20 and Cpn60 Interactors By Mass Spectr...supporting
confidence: 93%
“…For instance, HSP70 co-operates with CLP protease to deliver specific substrates for degradation [ 49 ]. Remarkably, the recent elucidation of the structure of the chloroplast CLP complex by cryoelectron microscopy in Chlamydomonas reinhardtii revealed that CPN60 chaperone forms a cap that represses CLP proteolytic activity, hence regulating protein folding and degradation [ 31 ]. Possibly, the CPN60 complex acts as an adaptor of CLP-delivering substrates.…”
Section: Protease-mediated Degradation In Chloroplastsmentioning
confidence: 99%